2015
DOI: 10.1002/art.39133
|View full text |Cite
|
Sign up to set email alerts
|

An Association Between Amino Acid Position 74 of HLA–DRB1 and Anti–Citrullinated Protein Antibody Levels in Japanese Patients With Anti–Citrullinated Protein Antibody–Positive Rheumatoid Arthritis

Abstract: Objective Anti–citrullinated protein antibodies (ACPAs) are highly specific to rheumatoid arthritis (RA), and strong associations between HLA–DRB1 alleles and ACPA levels have been detected in RA patients. We undertook this study to elucidate the associations between particular amino acid positions in HLA–DRB1 and ACPA levels in patients with RA. Methods We analyzed ACPA data on a total of 4,371 Japanese ACPA‐positive RA patients in whom HLA–DRB1 allele genotyping had been performed. Generalized linear regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 32 publications
5
14
0
Order By: Relevance
“…When we tested the associations of the imputed HLA variants, we found the most significant associations of HLA-DRB1 for each of the four ACPA-defined RA phenotypes (Figure 1 and Table S2). Within HLA-DRB1, amino acid polymorphisms of HLA-DRb1 showed the most significant risk, as previously reported; 7,8,10,11 the amino acid position 11 (or 13, in strong LD with the position 11 [r 2 ¼ 1.00 between Pro11 and Arg13 and 0.95 between Val11 and His13; Figure S1]) for ACPA-positive RA risk (p ¼ 1.7 3 10 À282 ; Figure 1A), position 71 for ACPA-negative RA risk (p ¼ 9.8 3 10 À11 ; Figure 1B), position 11 [or 13] for ACPApositive versus -negative RA (p ¼ 3.6 3 10 À57 ; Figure 1C), and position 74 for ACPA titer QTL (p ¼ 2.3 3 10 À45 ; Figure 1D). We note that HLA-DRb1 Ala71 is in strong LD with Pro11 and Arg13 (r 2 ¼ 0.95; Figure S1).…”
Section: Hla-drb1 Has the Largest Impact On Acpa-defined Ra Phenotypessupporting
confidence: 85%
See 1 more Smart Citation
“…When we tested the associations of the imputed HLA variants, we found the most significant associations of HLA-DRB1 for each of the four ACPA-defined RA phenotypes (Figure 1 and Table S2). Within HLA-DRB1, amino acid polymorphisms of HLA-DRb1 showed the most significant risk, as previously reported; 7,8,10,11 the amino acid position 11 (or 13, in strong LD with the position 11 [r 2 ¼ 1.00 between Pro11 and Arg13 and 0.95 between Val11 and His13; Figure S1]) for ACPA-positive RA risk (p ¼ 1.7 3 10 À282 ; Figure 1A), position 71 for ACPA-negative RA risk (p ¼ 9.8 3 10 À11 ; Figure 1B), position 11 [or 13] for ACPApositive versus -negative RA (p ¼ 3.6 3 10 À57 ; Figure 1C), and position 74 for ACPA titer QTL (p ¼ 2.3 3 10 À45 ; Figure 1D). We note that HLA-DRb1 Ala71 is in strong LD with Pro11 and Arg13 (r 2 ¼ 0.95; Figure S1).…”
Section: Hla-drb1 Has the Largest Impact On Acpa-defined Ra Phenotypessupporting
confidence: 85%
“…2,3 In particular, polymorphisms in HLA-DRB1 (MIM: 142857), one of the class II classical human leukocyte antigen (HLA) genes, are strongly associated with risk of ACPA-positive and -negative RA and with a quantitative trait locus (QTL) effect on serum ACPA titer. [4][5][6][7][8][9][10][11][12] Whether a genetic risk from these ACPA-defined RA phenotypes exists in the MHC region independently of HLA-DRB1 has long been a research question. 13 Recently, fine-mapping of the variants in the MHC region via HLA imputation 14,15 applied to genome-wide association studies (GWASs) or Immunochip SNP data has successfully identified an independent risk of ACPA-positive RA at multiple classical HLA genes in European populations (HLA-A [MIM: 142800], HLA-B [MIM: 142830], and HLA-DPB1…”
Section: Introductionmentioning
confidence: 99%
“…Considering the sample size in this study, power cannot explain the lack of association of genetic risk scores. Since HLA–DRB1 is strongly associated with ACPA positivity and ACPA levels in RA patients , the lack of associations between positivity for and levels of ACPAs and the finger SHS score seem to be consistent with the lack of association between HLA–DRB1 and the finger SHS score. Of note, the association patterns observed were not altered when we included the 24 Japanese patients in set 1 who were not registered due to having an excess SHS score (results not shown).…”
Section: Discussionmentioning
confidence: 59%
“…HLA-DRB1 is also associated with positivity for RF and ACPA [31] and levels of ACPA [32,33] but not for RF [34]. Non-SE alleles, such as HLA-DRB1*09:01 in Asian populations [32,33], have also been reported to be associated with RA [35] or ACPA levels, and the associations of HLA-DRB1 with ACPA levels are mainly explained by the 74th AA, alanine [32,33].…”
Section: Hlamentioning
confidence: 97%
“…HLA-DRB1 is also associated with positivity for RF and ACPA [31] and levels of ACPA [32,33] but not for RF [34]. Non-SE alleles, such as HLA-DRB1*09:01 in Asian populations [32,33], have also been reported to be associated with RA [35] or ACPA levels, and the associations of HLA-DRB1 with ACPA levels are mainly explained by the 74th AA, alanine [32,33]. Intriguingly, differences in genetic backgrounds between ACPA-positive and ACPA-negative RA were highlighted by a clear difference in signals at the HLA region [36], and such differences can also be explained by the same HLA-DRβ1 AA positions but different risk-associated residues [30].…”
Section: Hlamentioning
confidence: 98%